Modal Sosial Dan Ketahanan Ekonomi Masyarakat Terdampak Erupsi Gunung Semeru - Purwantiningsih , Ary; Puryanto, Sidik (PERSPEKTIF, 2024)
he eruption of Mount Semeru has caused significant material and physical losses, as well as created uncertainty and crises across various sectors, both economic and social. The impacts of lava flows, volcanic ash, and hot debris during the eruption not only damaged property and infrastructure but also destroyed social capital which is crucial for community resilience. The resulting economic uncertainty has raised concerns about the future and hindered efforts to revitalize affected sectors. Communities that have lost jobs become vulnerable to poverty, and the loss of infrastructure slows economic recovery. Social capital, which includes social networks, norms, and trust among community members, plays a critical role in the recovery process. This research aims to describe the relationship between social capital and economic resilience among survivors of the eruption in Lumajang, East Java. The research employs a descriptive method, with data collected through questionnaires and structured interviews. The results show that communication and social involvement among survivors remain limited and tend to focus on the family circle. Participation in community groups and the giving and receiving of support from social networks are still low. However, involvement in community groups positively affects the frequency of participation, requests for and provision of assistance, and reception of various types of support. Social support is considered very important and beneficial in daily life, especially in the context of disaster recovery. The study concludes that a deep understanding of how to strengthen social capital and integrate it into economic recovery strategies is an urgent need to create a supportive social environment for sustainable and resilient economic recovery following a natural disaster.